13C Natural Abundance of Serum Retinol Is a Novel Biomarker for Evaluating Provitamin A Carotenoid-Biofortified Maize Consumption in Male Mongolian Gerbils. Issue 7 (8th June 2016) - Gannon, Bryan M; Pungarcher, India; Mourao, Luciana; Davis, Christopher R; Simon, Philipp; Pixley, Kevin V; Tanumihardjo, Sherry A
Abstract: Background: Crops such as maize, sorghum, and millet are being biofortified with provitamin A carotenoids to ensure adequate vitamin A (VA) intakes. VA assessment can be challenging because serum retinol concentrations are homeostatically controlled and more sensitive techniques are resource-intensive. Objectives: We investigated changes in serum retinol relative differences of isotope amount ratios of 13 C/ 12 C (δ 13 C) caused by natural 13 C fractionation in C3 compared with C4 plants as a biomarker to detect provitamin A efficacy from biofortified (orange) maize and high-carotene carrots. Methods: The design was a 2 × 2 × 2 maize (orange compared with white) by carrot (orange compared with white) by a VA fortificant (VA+ compared with VA−) in weanling male Mongolian gerbils ( n = 55), which included a 14-d VA depletion period and a 62-d treatment period (1 baseline and 8 treatment groups; n = 5−7/group). Liver VA and serum retinol were quantified, purified by HPLC, and analyzed by GC combustion isotope ratio mass spectrometry for 13 C. Results: Treatments affected liver VA concentrations (0.048 ± 0.039 to 0.79 ± 0.24 μmol/g; P < 0.0001) but not overall serum retinol concentrations (1.38 ± 0.22 μmol/L). Serum retinol and liver VA δ 13 C were significantly correlated ( R 2 = 0.92; P < 0.0001). Serum retinol δ 13 C differentiated control groups that consumed white maize and white carrots (−27.1 ± 1.2 δ 13 C‰) from treated groups that consumed orange maize and white carrots (−21.6 ± 1.4 δ 13 C‰ P < 0.0001) and white maize and orange carrots (−30.6 ± 0.7 δ 13 C‰ P < 0.0001). A prediction model demonstrated the relative contribution of orange maize to total dietary VA for groups that consumed VA from mixed sources. Conclusions: Provitamin A efficacy and quantitative estimation of the relative contribution to dietary VA were demonstrated with the use of serum retinol δ 13 C. This method could be used for maize efficacy or effectiveness studies and with other C4 crops biofortified with provitamin A carotenoids (e.g., millet, sorghum). Advantages include no extrinsic tracer dose, 1 blood sample, and higher sensitivity than serum retinol concentrations alone.